The Influence of Sharia Financial Literacy on Financing Decision-Making In Sharia Banks: A Case Study of Customers In Palopo City - Hatima (LP2M IAIN Palopo, 2025)
This study aims to analyze the influence of Islamic financial literacy on financing decision-making in Islamic banks, with a focus on customers in Palopo City. The study used a quantitative method with a descriptive and causal approach, and involved 126 respondents who were selected through purposive sampling techniques. The results of the study show that Islamic financial literacy has a significant and positive influence on financing decisions, with a path coefficient value of 0.765. The level of understanding of Islamic financial principles, such as the prohibition of riba, gharar, and maysir, has been proven to affect customer preferences for sharia-based financing products. Respondents who have a higher level of education and middle income show a better level of Islamic financial literacy, so they are better able to make financing decisions in accordance with sharia principles. However, there are still challenges in improving Islamic financial literacy, especially among young respondents and those with lower education. This study suggests the need for a more structured Islamic financial literacy education program, as well as collaboration between Islamic banks, regulators, and educational institutions to increase Islamic financial inclusion in Indonesia.